(untitled) (The Pakistan Development Review, 2011)
High economic growth, extremely low nominal interest rate and negative real interest rate gave a boost to financial leverage (gearing ratio) of the textile sector to its peak in 2005. Firms are now are facing the consequence of high gearing. An explosion in their financing costs along with removal of textile quota from 2005 onwards and later on an acute energy crisis hampered their profitability and ability to repay their debt. This in turn contributed to non-performing loans which is now is likely to pose a big challenge for financial sector and push economy into another crisis. Most of the previous studies including a very few on capital structure of Pakistani firms focus on understanding only the firm specific determinants of financial leverage and completely ignore macroeconomic or institutional factors. Findings of this paper prove that all firm specific determinants including profitability and efficiency, firms‘ growth, risk and collateral excluding size significantly influence corporate financial leverage of textile industry in Pakistan. All macroeconomic variables including overall economic growth, equity market conditions and nominal cost of debt also have significant impact on corporate gearing. Negative sign with the composite measure of profitability and efficiency implies that banks are compelled to fund inefficient and unprofitable firms because demand for loans comes more from inefficient and unprofitable firms. Positive sign with growth and negative sign with risk is indicative of the fact that banks prefer to lend to growing rather than riskier firms. JEL classification: C13, C23, C51, L65, G10, G30 Keywords: Capital Structure Determinants, Corporate Financial Leverage, Corporate Gearing Ratio